Analisis Hubungan Karakteristik Sedimen dan Kandungan Bahan Organik Terhadap Distribusi Makrozoobentos di Desa Pambang Pesisir Kabupaten Bengkalis - Azuga, Nabila Afifah; Fauzan, Ikhwan; Ilahi, Ilham; Zulkifli, Zulkifli; Khaira, Annisa Ulfa; Sari, Gita Purnama (Master Program of Aquatic Resources Management, Department of Aquatic Resources, Undip, 2025)
This study was conducted in Desember 2024 in the Pambang Pesisir village Bengkalis Regency in Desember 2024, aiming to determine the size of sediment grains and the abundance of macrozoobentos and analyze the relationship of the sediment grain size and macrozoobentos abundance. The method used in this study is a survey method, namely samples taken directly from the waters and then analyzed in the laboratory. The research location was divided into 3 stations with 5 sampling point at each stasion. Sampling using a cement spoon spatula with 1x1 square meter. The average diameter of the sediment at station I is 5,23-5,56Ø which is classified as silt, with macrozoobentos abundance ranging from 7-10 ind/m2. Station II has an average sediment diameter of 5,36-7,20 which is classified as silt with an average macrozoobentos abundance ranging from 3-7 ind/m2. While station III ranges from 2,33-7,16 classified as fine sand to silt with macrozoobentos abundance ranging from 5-10 ind/m2. Based on this study, sediment grain size with macrozoobentos abundance has a strong relationship with a coefficient determination (R2) of 0,5870 and a correlation coefficient (r) of 0,619. The finer the sediment grain size, the higher the abundance of macrozoobentos, and vice versa.